PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP SEMANGAT KERJA PEGAWAI DI PT. PELAYARAN NASIONAL INDONESIA (PERSERO) CABANG MEDAN - Aminuddin Aminuddin; Fauzi Fauzi (Universitas Methodist Indonesia, 2021)
The formulation of the problem in this thesis is how the influence of leadership on employee morale at PT. Pelayaran Nasional Indonesia (Persero) Cabang Medan, the influence of motivation on employee morale at PT. Pelayaran Nasional Indonesia (Persero) Cabang Medan, the influence of leadership and motivation on employee morale at PT. Pelayaran Nasional Indonesia (Persero) Medan Branch. The purpose of this study was to determine and analyze the influence of leadership on employee morale at PT. Pelayaran Nasional Indonesia (Persero) Cabang Medan, the influence of motivation on employee morale at PT. Pelayaran Nasional Indonesia (Persero) Cabang Medan, the influence of leadership and motivation on employee morale at PT. Pelayaran Nasional Indonesia (Persero) Medan Branch. The population in this study were all employees of PT. Pelayaran Nasional Indonesia (Persero) Branch Medan, amounting to 50 employees, and the sample is the total population. Data was obtained through agency data, library data, and literature. The writer used data collection techniques through interviews and document studies. The data analysis technique was done by the writer through the descriptive analysis method and multiple linear regression analysis methods. The results of this study explain that leadership has a positive and significant effect on morale. With this kind of relationship, it means that interest has a positive and significant effect on morale. Good leadership will be able to increase the morale of PT. Pelayaran Nasional Indonesia (Persero) Medan Branch and vice versa poor leadership will worsen the morale of PT. Pelayaran Nasional Indonesia (Persero) Medan Branch. Motivation has a positive and significant effect on the morale of PT. Pelayaran Nasional Indonesia (Persero) Medan Branch. Leadership and motivation affect the morale of PT. Pelayaran Nasional Indonesia (Persero) Medan Branch. Thus, together (multiple) there is a positive and significant influence of leadership and motivation on the morale of PT. Pelayaran Nasional Indonesia (Persero) Medan Branch.